Eco-friendly synthesis of zinc oxide nanoparticles using Rivina humilis leaf extract and their biomedical applications. (January 2022) - Annapoorani, Angusamy; Koodalingam, Arunagirinadhan; Beulaja, Manikandan; Saiprasad, Gowrikumar; Chitra, Palanivel; Stephen, Arumainathan; Palanisamy, Subramanian; Prabhu, Narayanasamy Marimuthu; You, SangGuan; Janarthanan, Sundaram; Manikandan, Ramar
Graphical abstract: Highlights: ZnO nanoparticles were synthesized by a low-cost green Rivina humilis technique. FESEM and TEM images conferred the irregular and circular morphology of ZnONPs. XRD analysis confirmed that ZnONPs were crystalline in nature. The synthesized ZnONPs are effective in antioxidant and antibacterial activity. ZnONPs induced apoptotic mediated cell death in neuroblastoma cells. Abstract: In this study, we synthesized zinc oxide nanoparticles (ZnONPs) using aqueous leaf extract from Rivina humilis and its functions such as antioxidant, antibacterial and anticancer activities were investigated. ZnONPs were further characterized by UV–vis spectrophotometric analysis (UV–vis), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Field emission scanning electron microscope (FESEM), Transmission electron microscope and Energy dispersive X-ray spectroscopy (EDX). The synthesized ZnONPs exhibited a strong SPR peak at 370 nm. The XRD results confirming that the ZnONPs were crystalline in nature. Electron microscopic data depicted that these nanoparticles were irregular and circular in appearance with a size of 14.4 nm. The ZnONPs exhibited remarkable antioxidant activities than the extract of R. humilis . The antibacterial effect of ZnONPs against bacterial species was determined by agar diffusion assay. Further, Neuro 2a neuroblastoma cells indicated a dose-dependent decrease of viable cells when exposed to ZnONPs (5–100 μg/ml). ZnONPs induces a huge amount of lipid peroxidation end product malondialdehyde thus driving the cancer cells to be apoptosis. Moreover, treatment of Neuro 2a cells with ZnONPs brings about activation of apoptotic cell death through the intrinsic mitochondrial pathway by overexpressing caspases 3 and 9 while the reduction in Bcl-2 and upregulation of Bax protein.